2020
DOI: 10.3390/md18090475
|View full text |Cite
|
Sign up to set email alerts
|

Diphlorethohydroxycarmalol Attenuates Palmitate-Induced Hepatic Lipogenesis and Inflammation

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease, encompassing a range of conditions caused by lipid deposition within liver cells, and is also associated with obesity and metabolic diseases. Here, we investigated the protective effects of diphlorethohydroxycarmalol (DPHC), which is a polyphenol isolated from an edible seaweed, Ishige okamurae, on palmitate-induced lipotoxicity in the liver. DPHC treatment repressed palmitate-induced cytotoxicity, triglyceride content, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…In particular, DPHC is phlorotannin isolated from the EtOAc fraction of IOE, and DPHC was confirmed to be the main compound from the result of high performance liquid chromatography (HPLC) of the EtOAc fraction [37], and it was reported that it is the main compound showing various bioactivities via HPLC [34][35][36]38]. In addition, DPHC has been reported that exhibit anti-inflammatory activity [39][40][41], and it has also been reported to exhibit various bioactivities by regulating NF-κB signaling pathways, are a major pleiotropic transcription factor modulating immune, inflammatory, cell survival, and proliferative responses [35,[42][43][44]. IPA, another novel main phlorotannin identified from I. okamurae, was recently found to be involved metabolism such as diabetes and fat accumulation [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, DPHC is phlorotannin isolated from the EtOAc fraction of IOE, and DPHC was confirmed to be the main compound from the result of high performance liquid chromatography (HPLC) of the EtOAc fraction [37], and it was reported that it is the main compound showing various bioactivities via HPLC [34][35][36]38]. In addition, DPHC has been reported that exhibit anti-inflammatory activity [39][40][41], and it has also been reported to exhibit various bioactivities by regulating NF-κB signaling pathways, are a major pleiotropic transcription factor modulating immune, inflammatory, cell survival, and proliferative responses [35,[42][43][44]. IPA, another novel main phlorotannin identified from I. okamurae, was recently found to be involved metabolism such as diabetes and fat accumulation [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…51 This study illustrated that the SREBP1c expression controlled several downstream-signaling components, including FAS and SD1 , consistent with other studies. 6,7,49,51 Besides, the above components were significantly upregulated in PA induction, which subsequently increased the TG content. However, DHA treatment could reverse these aberrant trends.…”
Section: Discussionmentioning
confidence: 99%
“…, FAS and SCD1). 6,49,50 In obese mice induced by diet, it exerted anti-hepatic steatosis effects when the activity of SREBP-1c was inhibited. 7 Similarly, liver-specific SREBP-1c knockout mice indicated that the expression levels of lipogenic-related enzymes, including ACC1, FASN and SCD1, were significantly reduced, and the hepatic lipid content and TG plasma levels were lower than those of wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations